National Prevalence of Obesity: Prevalence of overweight and obesity in Sri Lankan adults - Katulanda, P.; Jayawardena, M.A.R.; Sheriff, M.H.R.; Constantine, G.R.; Matthews, D.R. (John Wiley & Sons, 2010)
Summary The aim of the study was to determine the prevalence of overweight, obesity and abdominal obesity, and the underlying socio-demographic correlates among Sri Lankan adults. Data were from 4532 adults aged ≥18 years randomly selected for a national level study on diabetes and cardiovascular disease. Weight, height and waist circumference (WC) were measured and body mass index (BMI) calculated. The mean (95% confidence interval) BMI and WC were 21.1 kg m−2 (20.9–21.3), 22.3 kg m−2 (22.1–22.4) and 78.0 cm (77.5–78.6) and 77.5 cm (77.0–78.0) for males and females, respectively. According to the proposed World Health Organization cut-off values for Asians, the percentage of Sri Lankan adults in the overweight, obese and centrally obese categories were 25.2%, 9.2% and 26.2%, respectively. Based on the cut-offs for Caucasians, these were 16.8%, 3.7% and 10.8%. Our findings were compatible with prevalence of obesity in regional countries. In addition, female sex, urban living, higher education, higher income and being in the middle age were shown to be associated with overweight and obesity in Sri Lankans. In conclusion, we have documented a relatively high prevalence of overweight and obesity, particularly, abdominal obesity among adults in Sri Lanka which is a middle-income country. Urgent public health interventions are needed to control the problem at an early stage.
Obesity reviews: 2010; 11(11); 751-756p.
Keywords: BMI; obesity; socio-demographic factors; Sri Lanka